A DECONSTRUCTIONIST READING OF TARIQ ALI’S SHAODWS OF THE POMEGRANATE TREE (1992) - Malik, Waseem Hassan; Sadia, Baby; Akram, Muhammad (European Scientific Journal, ESJ, 2014)
Tariq Ali in his post-colonial novel Shadows of the Pomegranate Tree (1992) attempts to provide a counter narrative against the West’s Orientalist view of the Muslims culture and their history. However, the novel is replete with silences, gaps and contradictions which seem to counter the text’s own agenda. Hence, it leads us to question the text’s ability in presenting its agenda properly and convincingly. The objective of the present study is to analyze the novel against the theory of deconstruction. The novel has been analyzed on the following grounds. Firstly, the text is an entity which is characterized by ambiguities, indecisiveness, and gaps which hinder to convey a single stable message or meaning and ultimately harm its main ideological project. Secondly, the hierarchical oppositions on which the text’s stability relies are arbitrary or illusionary; hence, it undermines the ideology that a text asserts. The study finds that the text, by not focusing on the intellectual aspect of the Muslims and by highlighting the erotic and sensual aspect of their personalities, harms its own ideological project which is to reject the West’s Orientalist view about the Muslims. In addition to this, the binary oppositions, on which the text’s main ideology stands that is the ‘tolerant and civilized Muslims’ and ‘intolerant and uncivilized Christians’ because of being unstable, undermine the text’s main ideology. Ultimately, the intended or desired message of the text is not conveyed.